MENGURAI INTELEKTUALITAS IMAM AL-BAZZAR DALAM KITAB MUSNADNYA - Andris Nurita (IAIN Kediri, 2020)
In term of to keep the autenticity of hadith, many prominent scholars have attempted to canonize Islamic traditions within a book. Besides, as the ages go on, not a few works of hadith scholars who were at first popular become less well known to academics. Among them is the book of a musnad written by Imam al-Bazzar with some its uniqueness. This study aims to examine the methods and contributions of the Imam al-Bazzar in his work so that it can be referred and read by muslims all over the world. This study methodÂ is descriptive methods in the form of verbal narratives based on data cited directly form the musnad. In term of the compiling of the book of musnad. Imam al-Bazzar begins by mentioning hadith-hadith narrated by ten friends guaranteed to go to heaven and then followed by the friends of the prophet Muhammadâ€™s family. He narrated a number of hadiths which are not mentioned in the book of nine. In addition, al-Bazzar also studied deeply unfixed hadiths, both visible and hidden. Thus, the book of musnad al-Bazzar makes a very large contribution in the islamic world and can be referred to by the next generation to the present day.Keywords: Method, contribution al-Bazzar